To find the zeroes we set #y# to #0# giving:
#0 = -3x^2 - 2x - 18#
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For #color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0#, the values of #x# which are the solutions to the equation are given by:
#x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))#
Substituting:
#color(red)(-3)# for #color(red)(a)#
#color(blue)(-2)# for #color(blue)(b)#
#color(green)(-18)# for #color(green)(c)# gives:
#x = (-color(blue)((-2)) +- sqrt(color(blue)((-2))^2 - (4 * color(red)(-3) * color(green)(-18))))/(2 * color(red)(-3))#
#x = (2 +- sqrt(4 - (216)))/(-6)#
#x = (2 +- sqrt(-212))/(-6)#
#x = (2 +- sqrt(4 * -53))/(-6)#
#x = (2 +- sqrt(4)sqrt(-53))/(-6)#
#x = (2 +- 2sqrt(-53))/(-6)#
#x = (1 +- 1sqrt(-53))/(-3)#
#x = (1 +- sqrt(-53))/(-3)#